Nursing Care for Unstable Angina Pectoris with the Intervention of Foot Massage Techniques to Reduce Pain Scale - Iif Taufiq El Haque; Asep Gunawan; Nur Hidayat; Elza Dwi Zuvita (LPPM STIKes Muhammadiyah Ciamis, 2021)
Unstable angina pectoris or angina sitting is a chronic syndrome in which the client gets a typical attack of left chest pain, which is like being pressed or stabbed. Based on data from the World Health Organization (WHO) in 2015, it showed that as many as 17.5 billion people in the world died from cardiovascular disease. Indonesia ranks fourth as the country with the highest number of deaths from cardiovascular disease. The main symptom that often appears is chest pain, and one of the non-pharmacological techniques that can be used to reduce pain is non-pharmacological foot massage. The objective of this study is to present care with foot massage technical interventions to overcome chest pain scales and pain scale measurement tools using the Numerical Rating Scale (NRS) for unstable Angina Pectoris clients with acute pain in the Memory Room of the Banjar City Hospital. The research design method used is descriptive analysis with a case study approach. Subjects in this case study were adult patients who experienced unstable angina pectoris with acute pain problems. Data collection techniques include interviews, observation, physical examination, and documentation studies. Result The results of the case study at the assessment stage found that the client complained of chest pain. The intervention and implementation used to reduce chest pain is giving foot massage techniques for 60 minutes when chest pain complaints occur. After the intervention, the client's pain scale decreased from 4 (0–10) to 1 (0–10), while subjective data from anamnesis showed that the client said chest pain had decreased. Conclusion The conclusion of nursing care for patients who experience unstable angina pectoris with chest pain problems is well resolved. Intervention with foot massage technique is effective against pain scale.